Энергосистемы на базе возобновляемых источников энергии - Гуров, В. И. (Eastern-European Journal of Enterprise Technologies, 2009)
Problems rendering technologies for airaccumulating power stations and possibility of realized projects are considered. The attention is paid to the decision of a problem of working out energy-transuding product-gas at recycling of a firm household waste